Evaluation of Citizen Partner Program in State High School 13 Surabaya - Roesminingsih, Maria Veronika; Handayaningrum, Warih; Husna, Nafi’ Sayyidatul (Universitas Malikussaleh, 2020)
The development of education in Indonesia must use at least four basic strategies. Namely, The first is equitable distribution of opportunities for education; the second is relevance; the third is quality improvement, and the fourth is efficiency. Generally, this strategy can be divided into two dimensions, namely education improvement and equity. Development of quality improvement is expected to increase the efficiency, effectiveness and productivity of education.